2011 Triennial Surveillance Review : Staff Background Studies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper evaluates the IMF's exchange rate analysis since the 2008 TSR. It focuses on the evolution of methods, the quality of the IMF's multilateral and bilateral exchange rate analysis, the evenhandedness and transparency of this analysis, and the need to improve the coverage and integration of external stability assessments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet